2017
DOI: 10.1093/annonc/mdx122
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase III trial of S-1 versus capecitabine in the first-line treatment of metastatic colorectal cancer: SALTO study by the Dutch Colorectal Cancer Group

Abstract: NCT01918852.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 20 publications
3
61
0
Order By: Relevance
“…An alternative treatment option could be S1, which is an oral fluoropyrimidine only registered for use in a palliative setting that includes three different agents: tegafur, gimeracil, and oteracil. S1 is associated with a significantly lower incidence of hand-foot syndrome compared with capecitabine, with comparable efficacy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative treatment option could be S1, which is an oral fluoropyrimidine only registered for use in a palliative setting that includes three different agents: tegafur, gimeracil, and oteracil. S1 is associated with a significantly lower incidence of hand-foot syndrome compared with capecitabine, with comparable efficacy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that bevacizumab was not administered in 41% to 49% of Dutch patients as part of first-line treatment for metastatic colorectal cancer. 12,13 Therefore, the aim of our provider-based study was to compare the reported use of adjuvant and metastatic colorectal treatment regimens with the recommendations in the most recent Dutch colorectal cancer guideline.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, S-1 treatment was associated with lower rates of some important adverse events including fewer catheter-related complications, grade 3–4 mucositis, stomatitis, febrile neutropenia, dehydration, and toxicity-related deaths than 5-FU, and fewer cases of grade 3–4 neutropenia and grade 1–2 HFS compared with capecitabine [ 9 ]. Similarly, in a recent phase III study that compared the incidence of HFS in patients with metastatic colorectal cancer treated with oral capecitabine vs. S-1, efficacy was similar but rates of HFS were significantly lower for patients who received S-1 compared with capecitabine (45% vs. 73%; p = 0.0005) [ 12 ].…”
Section: Introductionmentioning
confidence: 94%